Validation of Cybersecurity Framework for Threat Mitigation - Llanten-Lucio, Yeison-Isaac; Amador-Donado, Siler; Marceles-Villalba, Katerine (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Currently on the Internet there are many threats that threaten the security of the information of users who daily access this network using different devices that connect from their homes or organizations that in many cases do not have security controls enough and end up exposing themselves to all those threats that grow over time. That is why this article aims to propose the validation of a cybersecurity framework that allows mitigating and reducing risks to increase security levels through the implementation of controls for homes and organizations using emerging technologies such as: IoT, Blockchain and Deep Learning. The foregoing was carried out with the methodological approach of action research starting from the improvement of the process in search of transformation, thus obtaining as results the integration of the aforementioned methodologies for the detection of possible malicious hosts within an internal network through an intelligent analysis of the traffic that passes through the same network in order to intelligently generate rules in intrusion detection systems (IDS) in an automated way and that these rules can in turn be distributed through a secure channel using the Blockchain technology, to finally guarantee the integrity of said rules and that also allows maintaining the immutability and synchronization of the same information with all the devices connected to the framework.